Effect of Wound Care Using Robusta Coffee Powders on Diabetic Ulcer Healing - Yeni Yeni Yulianti; Kusman Ibrahim; Titis Kurniawan (Faculty of Nursing Universitas Padjadjaran, 2018)
Diabetic Gangrene Ulcers are chronic wounds with proinflammatory wound environment caused by elevated levels of TNF-α, which tends to occur in delay in wound healing, and infection susceptibility. This research aims to determine the effect of wound care using Robusta coffee powder as an adjuvant to the healing of diabetic ulcers gangrene.32 patients were included in this Quasi-experiment with Pretest-Posttest Control Group Design approach and the sampling was done by consecutive sampling method at random. The object was divided into 2 groups, namely the intervention group and the control group performed on patients undergoing treatment in the surgical and inpatient wards, Regional public hospital, Sekarwangi. The intervention group received wound treatment with Robusta coffee powder while the control group received conventional wound treatment for 2 weeks, during which also has been done assessment of wound scores with wound assessment Bates Jensen at the time of pretest and posttest. Characteristics of respondents between the intervention group and the homogeneous control did not differ significantly. The difference of mean score of pretest and posttest score in two groups with t test showed there was significant difference with p value <0,05, whereas for difference of mean score between group of intervention and control with independent t test showed there is difference significantly. There is influence of wound care using Robusta coffee powder as adjuvant to healing diabetic ulcers gangrene in Regional public hospital, Sekarwangi, Sukabumi. Therefore, it is important for the hospital to consider wound care using Robusta coffee powder on diabetic ulcer gangrene wounds as it can accelerate wound healing. Keywords: Robusta cofee, Wound healing, Diabetic ulcers, Wound assessment Bates Jensen